2010
DOI: 10.1002/dvdy.22513
|View full text |Cite
|
Sign up to set email alerts
|

β8 integrin and band 4.1B cooperatively regulate morphogenesis of the embryonic heart

Abstract: *Morphogenesis of the heart is regulated by various cues, including growth factors and extracellular matrix (ECM) proteins. The mechanisms by which cardiac cells properly integrate these cues to regulate growth, differentiation, and migration remain poorly understood. Here we have used genetic strategies in mice to identify avb8 integrin and its cytoskeletal adaptor protein, Band 4.1B, as essential regulators of cardiac morphogenesis. We demonstrate that approximately 60% of mouse embryos genetically null for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…FITC-conjugated phalloidin was purchased from Sigma. The anti-αv integrin and anti-β8 integrin rabbit polyclonal antibodies used for immunoblotting have been described elsewhere (24, 25). Secondary antibodies were goat anti-rabbit, goat anti-chicken, goat anti-rat and goat anti-mouse, all conjugated to Alexa488 or Alexa594 (Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%
“…FITC-conjugated phalloidin was purchased from Sigma. The anti-αv integrin and anti-β8 integrin rabbit polyclonal antibodies used for immunoblotting have been described elsewhere (24, 25). Secondary antibodies were goat anti-rabbit, goat anti-chicken, goat anti-rat and goat anti-mouse, all conjugated to Alexa488 or Alexa594 (Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%
“…Integrins have been shown to regulate morphogenesis, angiogenesis, heart remodeling, and neuritogenesis. [125][126][127] For example, integrin a5 and aV were not required in endothelial cells for initial vasculogenesis and angiogenesis but they were significantly involved in the remodeling of the heart and great vessels. 126 It was also shown that b1 integrin played a critical role in skeletal myoblast response to stretch by activating the downstream effector FAK.…”
Section: Stretch Signaling Pathwaysmentioning
confidence: 99%
“…There is increasing evidence for a role for interactions between the 4.1 proteins and integrins (22,(51)(52)(53)(54). Data in Fig.…”
Section: Discussionmentioning
confidence: 98%